2006
DOI: 10.1097/01.jcp.0000237947.80764.d9
|View full text |Cite
|
Sign up to set email alerts
|

The Early Effect of Olanzapine and Risperidone on Insulin Secretion in Atypical-naïve Schizophrenic Patients

Abstract: Recently, increasing attention has been drawn to the potential diabetogenic effect of atypical antipsychotics. The goal of this prospective study is to evaluate the early effect of olanzapine and risperidone treatment on pancreatic beta-cell function in atypical-naive schizophrenic patients. Twenty-six subjects were assigned randomly to therapy with olanzapine or risperidone for 14 days. The metabolic parameters were quantitatively assessed by using the intravenous glucose tolerance test. The levels of fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(40 citation statements)
references
References 24 publications
2
36
1
1
Order By: Relevance
“…Different antipsychotics have varying propensities to induce weight gain, dyslipidemia and diabetes (7,(18)(19)(20)(21)(22). Atypical antipsychotics are also known to exacerbate pre-existing and emerging cardiovascular disease and diabetes risk factors in patients with schizophrenia (23,24).…”
Section: Resultsmentioning
confidence: 99%
“…Different antipsychotics have varying propensities to induce weight gain, dyslipidemia and diabetes (7,(18)(19)(20)(21)(22). Atypical antipsychotics are also known to exacerbate pre-existing and emerging cardiovascular disease and diabetes risk factors in patients with schizophrenia (23,24).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous subsequent prospective trials of olanzapine-treated patients (Eder et al, 2001;Graham et al, 2005b;Ebenbichler et al, 2005;Murashita et al, 2005;Hosojima et al, 2006) and clozapine-treated patients (Monteleone et al, 2002;Kivircik et al, 2003;Sporn et al, 2005;Theisen et al, 2005) confirmed the association between use of these medications, weight gain, and increased serum leptin levels. For agents with less weight gain liability, such as high potency typicals (Hagg et al, 2001;Atmaca et al, 2003a;Atmaca et al, 2003c), sulpiride (Baptista et al, 2000), quetiapine (Atmaca et al, 2003c), or risperidone (Fitzgerald et al, 2003;McIntyre et al, 2003;Martin et al, 2004;Chiu et al, 2006), comparative trials noted modest weight gain and leptin changes, while olanzapine and clozapine exposed subjects experienced marked increases in adiposity, weight and serum leptin. A few prospective trials which examined the effect of pharmacological weight-modifying strategies using adjunctive amantadine (Graham et al, 2005a) or nizatidine (Atmaca et al, 2003b;Atmaca et al, 2004) found positive effects of the adjunctive medication, with proportional differences in leptin levels compared to those treated with antipsychotic alone.…”
Section: Leptin Drug Effectsmentioning
confidence: 99%
“…Several antipsychotic studies measured metabolic outcomes along with serum leptin levels, but did not specifically calculate correlation coefficients between leptin and other parameters (Baptista et al, 2001;Eder et al, 2001;Atmaca et al, 2003a;Melkersson and Dahl, 2003;Graham et al, 2005a;Graham et al, 2005b;Smith et al, 2005;Sporn et al, 2005;Chiu et al, 2006;Hosojima et al, 2006;Atmaca et al, 2007). Nonetheless, in many instances leptin levels increased significantly without significant changes in serum insulin, other glycemic or lipid measures (Zhang et al, 2004;Murashita et al, 2005;Sporn et al, 2005;Chiu et al, 2006;Hosojima et al, 2006;Atmaca et al, 2007). One cross-sectional study in bipolar subjects also found no correlation between any glucose or lipid parameter and leptin levels (Gergerlioglu et al, 2006), although a small number reported significant correlations between leptin and serum insulin (Baptista et al, 2000;Melkersson et al, 2000;Melkersson and Hulting, 2001), glucose (Wang et al, 2006) and serum triglycerides (Atmaca et al, 2003c); however, most of the authors reporting significant correlations did not control for BMI.…”
Section: Other Metabolic Parametersmentioning
confidence: 99%
“…One of them found results that favor risperidone (Cooper et al, 2008) and the other slightly favors risperidone, but clarifies that no statistical difference was found (De Ridder & De Graeve, 2009). The metabolic side effects of olanzapine are widely known and there is evidence that they are more prevalent with olanzapine than with other drugs (Rosenheck et al, 2003;Mcquade et al, 2004;Breier et al, 2005;Lieberman et al, 2005;Chiu et al, 2006;Fleischhacker et al, 2009;Kane et al, 2009;Alvarez et al, 2012;Ou et al, 2013;Zhang & Lan, 2014). When the developed model depends highly of metabolic effects, olanzapine tend to be in disadvantage when compared to aripiprazole, risperidone and ziprasidone (Colombo et al, 2008;Mcintyre et al, 2010).…”
Section: Qualitative Synthesismentioning
confidence: 99%